2014
DOI: 10.1242/jcs.152702
|View full text |Cite
|
Sign up to set email alerts
|

Leiomodin 3 and Tropomodulin 4 have overlapping functions during skeletal myofibrillogenesis

Abstract: Precise regulation of thin filament length is essential for optimal force generation during muscle contraction. The thin filament capping protein tropomodulin (Tmod) contributes to thin filament length uniformity by regulating elongation and depolymerization at thin filament ends. The leiomodins (Lmod1-3) are structurally related to Tmod1-4 and also localize to actin filament pointed ends, but in vitro biochemical studies indicate that Lmods act instead as robust nucleators. Here, we examined the roles of Tmod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 49 publications
(71 reference statements)
8
37
0
Order By: Relevance
“…and Lmod3 mRNAs were detected in all striated muscles, in agreement with previous studies (Cenik et al, 2015;Chereau et al, 2008;Conley et al, 2001;Nworu et al, 2015;Tian et al, 2015;Yuen et al, 2014), but an unexpected muscle type dependence was observed, with Lmod2 mRNA predominating in slow-twitch soleus, diaphragm, and left ventricular muscles and Lmod3 mRNA more highly expressed than Lmod2 mRNA in fast-twitch TA muscle (Fig. 1C).…”
Section: Gene Expression and Protein Abundance Of Sarcomeric Tmodssupporting
confidence: 92%
See 2 more Smart Citations
“…and Lmod3 mRNAs were detected in all striated muscles, in agreement with previous studies (Cenik et al, 2015;Chereau et al, 2008;Conley et al, 2001;Nworu et al, 2015;Tian et al, 2015;Yuen et al, 2014), but an unexpected muscle type dependence was observed, with Lmod2 mRNA predominating in slow-twitch soleus, diaphragm, and left ventricular muscles and Lmod3 mRNA more highly expressed than Lmod2 mRNA in fast-twitch TA muscle (Fig. 1C).…”
Section: Gene Expression and Protein Abundance Of Sarcomeric Tmodssupporting
confidence: 92%
“…4C), as expected (Nworu et al, 2015;Yuen et al, 2014). The Lmod3 striations were ∼0.95 µm from the Z-line (Fig.…”
Section: Deletion Of Tmod4 Alters the Expression Of Striated Muscle Lsupporting
confidence: 78%
See 1 more Smart Citation
“…Analysis of the proteome of skeletal muscle from Klhl40-mutant mice revealed pronounced downregulation of leiomodin-3 (LMOD3), a putative actin-nucleating protein that had not been previously studied (6). Subsequently, frame-shift and nonsense mutations in LMOD3 were found to cause nemaline myopathy in humans, and inhibition of Lmod3 in zebrafish and Xenopus through morpholino-mediated knockdown was shown to cause myofiber disarray (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The Lmods are structurally similar to the Tmods; however, they lack a second tropomyosin-binding domain and possess an extended C-terminal region containing an additional (third) actin-binding domain. Mutations in LMOD3 were recently discovered to underlie autosomal recessive nemaline myopathy, and Lmod3 is essential for myofibrillogenesis and/or organization of skeletal muscle thin filaments (Cenik et al, 2015;Tian et al, 2015;Nworu et al, 2015;Yuen et al, 2014; for review, see Sandaradura and North 2015). Furthermore, knockout of a different Lmod family member (Lmod2) reduces thin filament length in the heart and results in a rapid onset dilated cardiomyopathy (Pappas et al, 2015).…”
Section: Nebulin Interacting Partnersmentioning
confidence: 99%